Carrageenan Extraction of Kappaphycus alvarezii Seaweed from Nusa Lembongan Waters Using Different Alkaline Treatments - Ichoun Brawici Dhewang; Ervia Yudiati; Subagiyo Subagiyo; Rabia Alghazeer (Universitas Diponegoro, 2023)
Kappaphycus alvarezii is a carrageenan-producing red seaweed that is widely cultivated in Nusa Lembongan waters, Bali, Indonesia. Carrageenan is generally extracted using an alkaline base,. iIn this study three different types of alkali were used to extract carrageenan originating from Nusa Lembongan Waters. This study aims to determine the quality of the extraction. The three alkalis used were KOH, NaOH, Ca(OH)2, and distilled water as a control. The 20 g dried seaweed was weighed, washed with the tap running water, and immersed in 0.15% alkaline solution (KOH, NaOH, Ca(OH)2) as well as distilled water for 24 hrs. Followed by rinsing with running water until pH was neutral. The solution was soaked and heated at 100ºC for 2 hours with a ratio of seaweed and water 1 kg in 20 L, and filtered. The extract was mixed with 1.25% KCI. The carrageenan precipitate was put in the oven at 60-80ºC until dry for 48 hours. The yield test results showed that the use of alkaline Ca(OH)2 resulted in a yield of 29.28% better than alkaline KOH (28.18%) and NaOH (27.7%). Based on the analysis of Fourier Transform Infrared Spectroscopy (FTIR), extraction using alkaline Ca(OH)2 showed functional groups characteristic of iota-carrageenan, whereas using alkaline KOH and NaOH showed functional groups characteristic of kappa-carrageenan.